ANALISIS KESIAPAN SEKOLAH TERHADAP PERUBAHAN KURIKULUM Studi Kasus SMK Perindustrian Yogyakarta dan SMA Negeri 5 Yogyakarta - Rizka Puspitasari; Faizatin Nur Rahmah; Ahmad Adi Nugroho; Faizah Nur Khamidah; Moh. Slamet Sutrimo (Universitas Islam Negeri Alauddin Makassar, 2018)
Abstract:Curriculum is instrument of education on school to supporting goal of national education. The development of era demands the change of curriculum fore the sake of country development. Every country hope can compete with another country in the world. “The progress of country proportionate straiht with the progress of education”. Because of that, the figure of school as education instantion is very important to release the goal of national education. The school must be ready to confront the change of curriculum. the difference beetwen every curriculum makes a trouble in some aspect. Example: evaluation in curriculum 2013 more complex than curriculum KTSP. This matter needs a carefulness of teacher and increasing time of lesson. Because of that, every school must be fill the human resource and infrastructure to support education system.